Self-Administration of Entactogen Psychostimulants Dysregulates Gamma-Aminobutyric Acid (GABA) and Kappa Opioid Receptor Signaling in the Central Nucleus of the Amygdala of Female Wistar Rats - Khom, Sophia; Nguyen, Jacques D.; Vandewater, Sophia A.; Grant, Yanabel; Roberto, Marisa; Taffe, Michael A. (Frontiers in Behavioral Neuroscience, 2021)
Male rats escalate intravenous self-administration of entactogen psychostimulants, 3,4-methylenedioxymethcathinone (methylone) and 3,4-methylenedioxymethamphetamine (MDMA) under extended access conditions, as with typical psychostimulants. Here, we investigated whether female rats escalate self-administration of methylone, 3,4-methylenedioxypentedrone (pentylone), and MDMA and then studied consequences of MDMA and pentylone self-administration on GABAA receptor and kappa opioid receptor (KOR) signaling in the central nucleus of the amygdala (CeA), a brain area critically dysregulated by extended access self-administration of alcohol or cocaine. Adult female Wistar rats were trained to self-administer methylone, pentylone, MDMA (0.5 mg/kg/infusion), or saline-vehicle using a fixed-ratio 1 response contingency in 6-hour sessions (long-access: LgA) followed by progressive ratio (PR) dose-response testing. The effects of pentylone-LgA, MDMA-LgA and saline on basal GABAergic transmission (miniature postsynaptic inhibitory currents, mIPSCs) and the modulatory role of KOR at CeA GABAergic synapses were determined in acute brain slices using whole-cell patch-clamp. Methylone-LgA and pentylone-LgA rats similarly escalated their drug intake (both obtained more infusions compared to MDMA-LgA rats) however, pentylone-LgA rats reached higher breakpoints in PR tests. At the cellular level, baseline CeA GABA transmission was markedly elevated in pentylone-LgA and MDMA-LgA rats compared to saline-vehicle. Specifically, pentylone-LgA was associated with increased CeA mIPSC frequency (GABA release) and amplitude (postsynaptic GABAA receptor function), while mIPSC amplitudes (but not frequency) was larger in MDMA-LgA rats compared to saline rats. In addition, pentylone-LgA and MDMA-LgA profoundly disrupted CeA KOR signaling such as both KOR agonism (1mM U50488) and KOR antagonism (200nM nor-binaltorphimine) decreased mIPSC frequency suggesting recruitment of non-canonical KOR signaling pathways. This study confirms escalated self-administration of entactogen psychostimulants under LgA conditions in female rats which is accompanied by increased CeA GABAergic inhibition and altered KOR signaling. Collectively, our study suggests that CeA GABA and KOR mechanisms play a critical role in entactogen self-administration like those observed with escalation of alcohol or cocaine self-administration.